DIGITAL HERMENEUTICS OF THE QUR’AN : TANTANGAN TASFIR DI ERA ARTIFICIAL INTELLIGENCE - Aulia, Nizam Udin (Institut Agama Islam Negeri (IAIN) Ponorogo, 2025)
The rapid development of Artificial Intelligence (AI) has significantly transformed how people interact with information, including in the field of Islamic studies and Qur’anic interpretation. Today, technologies such as Natural Language Processing (NLP), machine learning algorithms, and digital platforms are increasingly being used to read, analyze, and even